Butyrylcholinesterase activity in dairy cows naturally infected by Dictyocaulus viviparous and treated with eprinomectin. (January 2017) - Pereira, Raquel; Silva, Aleksandro; Mendes, Ricardo; Bottari, Nathieli; Schwertz, Claiton; Lucca, Neuber; Henker, Luan; Morsch, Vera; Schetinger, Maria; Machado, Gustavo
Abstract The aim of this study was to evaluate the activity of butyrylcholinesterase (BChE) in dairy cows naturally infected byDictyocaulus viviparus and treated with eprinomectin. Among 22 serum samples, 10 were of animals with mild clinical disease and 12 with severe clinical disease. The samples were collect on days 0 (day of diagnosis) and 10 post-treatment (a single dose of eprinomectin [360 μg/kg, topically]). We evaluated the activity of BChE, alanine aminotransferase (ALT), aminotransferase andaspartate (AST), and gamma-glutamyl transferase (GGT) in serum. There was no significant difference between groups with different degrees of clinical disease (mild and severe) for the activity of BChE (p  > 0.05). However, when considering the treatment (before and after), a significant difference was identified in the activity of BChE (p  < 0.05), i.e., has a reduction in BChE activity post-treatment. No significant difference in the enzymatic activity of ALT, AST, and GGT between mild or severe disease, as well as pre- and post-treatment (p  > 0.05), was found. Based on these results, we can conclude that the treatmentD. viviparus leads to a decrease of BChE activity, probably due to decrease in the inflammatory response in response to clinical improvement.